Spatio-temporal unevenness in local land system regime shifts caused by land deals in Lao PDR - Nicholas R. Magliocca; Evan A. Ellicott; Micah L. Ingalls; Michael Epprecht; Cornelia Hett; Vong Nanhthavong; Ariane C. de Bremond (Ecology and Society, 2022)
Extensive land-use “regime shifts” have been observed as rapid transitions from natural land cover or subsistence-oriented land use to intensified and/or expanded commodity production. However, it is often unclear whether these land-use changes are part of broader land system regime shifts in which pre-existing production systems and livelihood strategies are fundamentally transformed along with observable land-use changes rather than simply displaced or eliminated. This is a critical social-environment question given that regime shifts are often a desired and intended outcome of national rural development and market-liberalization policies but must also be attentive to environmental conservation and/or climate change mitigation goals. We investigated whether nationally extensive land-use changes implemented through large-scale land deals in Lao People’s Democratic Republic resulted in full, partial, or no village- and landscape-level regime shifts in and around land deals. Overall, land deals triggered a wide variety of full, partial, and no regime shift outcomes. Land deals with both domestic and foreign investors produced positive and negative outcomes, although foreign land deals for the production of rubber led to significantly higher rates of indirect land-use change in impacted villages than domestic and/or non-rubber land deals. Also, financial compensation alone was insufficient to improve community well-being because it could be reinvested to perpetuate previous land uses without the desired transformation in livelihoods and rural development. Land deals that exhibited greater social embeddedness (i.e., provided adequate compensation complemented by job-creation and improved access to infrastructure and/or services) were more likely to lead to positive regime shifts. Our findings demonstrate that any land system regime shift will produce both winners and losers, and thus it becomes necessary to critically analyze the localized distribution of social and environmental costs and benefits within broader-scale land-use regime shifts.